The Influence of the School Field Trip on the Modification of Preconception of Scientific Terms - Chocholoušková, Zdeňka; Hajerová Müllerová, Lenka (Scientia in educatione, 2020)
The contribution of field trip is outlined in the realized research, which, through cognitive mapping, makes it possible to record a quantitative and qualitative change/shift in the content of selected scientific terms. Pupils with a deeper interest in biology who completed a one-day field trip developed concept maps before and after the field trip based on the terms presented (namely the ones they encountered during the field trip). At the same time, the pupils defined the terms before and after the excursion. Based on the verbal expression of terms and concept maps before and after the field trip, the number of terms before and after the excursion, the professionalism of their approach, the number and correctness of interconnections and the number of cross-links between terms were evaluated. Concept maps were analyzed using CMapTools and Gephi. Most pupils showed marked improvement after the field trip, having become familiar with more terminology and capable of more accurate structuring. However, there was hardly any shift in the use of linking words or expressing links between concepts.